Acute Leukemia - Alisherovna, Xaqqulova Marta; Rustam o’g’li, Zokiriy Abdulazim; Umid o’g’li, Umatillayev Sardor; Baxtiyorovna, Elmurotova Dilnoza (American Journal of Bioscience and Clinical Integrity, 2026)
This study demonstrates that bleeding gums are often the first clinical sign of acute leukemia, occurring with the slightest contact with the oral mucosa. Necrosis spreads rapidly, and soon an ulcer with a dirty, gray, foul-smelling plaque forms around the tooth. Necrosis is often detected in the tonsils, retromolar region, and other areas of the oral cavity. A characteristic feature of the necrotic process in acute leukemia is its tendency to spread to adjacent areas of the mucosa. Treatment of acute leukemia is performed in a specialized hematology department.